Incidence of Bacterial Vaginosis in Pregnancy at Tamangapa Health Center Makassar - Sartika; Haruna, Nadyah; Setiawati, Dewi; Rahim, Rosdianah; Hilal , Fatmawaty (Jurnal Midwifery, 2025)
Introduction Bacterial vaginosis (BV) is a condition where there is a change in the normal balance of bacteria in the vagina. This disorder is characterised by the excessive production of vaginal secretions that are plentiful, grey to yellow in colour, thin, uniform, and have a fishy odour. Additionally, there is an elevation in pH levels. Bacterial vaginosis (BV) is frequently observed in women who are of reproductive age, including those who are pregnant. The objective of this study is to ascertain the prevalence of bacterial vaginosis (BV) during pregnancy at Tamangapa Health Centre. Method this study is an exploratory study that aims to provide a detailed description and analysis of the subject matter. Data were gathered from pregnant women who underwent ANC examination and reported symptoms of vaginal discharge over the period of March-April 2024. These women also expressed their willingness to undergo vaginal swabbing. The vaginal swabs were subjected to gramme staining and evaluated using the Nugent criteria. The results were then displayed in a table showing the frequency distribution. Out of the 35 pregnant women who reported vaginal discharge according to Nugent’s criteria, an equal number of pregnant women were diagnosed with BV. Among these individuals, there were cases when vaginal discharge was present along with a diagnosis of BV. Conclusion out of the 35 pregnant women who participated, 13 of them had pathological fluor albus, and 8 of these women also had BV.